Metformin in Pregnancy with Diabetes-Opinions from Several Latest Guidelines - Ye Feng; Hui-Xia Yang; Yang Pan (Wolters Kluwer Health, 2020)
Abstract. Pregnancy complicated with diabetes is associated with adverse maternal and fetal outcomes. Good control of glucose level during pregnancy contributes to improve maternal and fetal outcomes and break the vicious cycle of "diabetes begetting diabetes". The first line antidiabetic drug in pregnancy is insulin, which is expensive and inconvenient to use. Lots of clinical trials and meta-analyses have constantly confirmed the safety and efficacy of metformin in pregnancy. Several guidelines across the world have been discussing metformin as an alternative to insulin in pregnancy. This article summarizes the opinions about metformin from several latest guidelines.